ISOLATION AND CHARACTERIZATION OF STEM CELLS FROM YOLK SAC DOMESTIC PORCINE (Sus scrofa) - Bertassoli, Bruno Machado; Santos, Amilton Cesar; Fratini, Paula; Will, Sonia Elizabete Alves de Lima; Rodrigues, Marcio Nogueira; Assis Neto, Antonio Chaves de (Archives of Veterinary Science, 2015)
Embryonic stem (ES) cells are pluripotent cells that are able to generate a whole organism. The ES cells give rise to rapidly dividing fetal stem (FS) cells, which are responsible for fetal growth and development. Therefore, this study aimed to analyze the cells from the yolk sac to characterize this cells as to potential as a possible source of pluripotent stem cells for future use in regenerative therapy. The yolk sac tissue was collected from the embryos in the early stage of gestation (30d) and explants from YS were plated with medium culture 15% fetal bovine serum and incubated at 37ºC in a humidified atmosphere of 5% CO2. Trials were made for concentration and cell viability, cell growth evaluation, and the characterization by flow cytometry using specific antibodies (CD105, NANOG, CD45 and Oct-3/4), immunocytochemistry using the following antibody: CD90, CD105, CD117, vimentin, Stro-1, Oct-4, VEGF, beta tubulin, Cytokeratin and PCNA and Osteogenic, adipogenic, and chondrogenic differentiation assays. The yolk sac cells showed adherence to plastic and a spindle-like morphology, they reached confluence of 70% in about 20 days, these cells were maintained until passage 4, where later cell death occurred. These cells had similar imunofenoipagem the mesenchymal stem cells and hematopoietic cells expressing markers such as CD105, CD90, CD117, vimentin, Stro-1, Oct-4, VEGF, Beta Tubulin, Cytokeratin, Nanog and PCNA. These cells can be classified as pluripotent cells, in other words, possessed self-renewal and multi-lineage differentiation potency, which could differentiate into chondrocytes, adipocytes and osteocytes. The pYS cells would provide an ideal cell resource for regenerative medicine and tissue engineering.